2004
DOI: 10.1016/j.jvs.2004.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid drainage to prevent paraplegia during thoracic and thoracoabdominal aortic aneurysm surgery: a systematic review and meta-analysis

Abstract: Evidence from randomized and nonrandomized trials and from cohort studies support the use of CSF drainage as an adjunct to prevent paraplegia when this adjunct is used in centers with large experience in the management of TAAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(100 citation statements)
references
References 40 publications
0
93
0
7
Order By: Relevance
“… Cerebrospinal fluid drainage (CSFD) which has a strong evidence basis underpinning its use, reducing the pressure of cerebrospinal fluid (CSF) surrounding the spinal cord and consequently increases spinal cord perfusion [2,[18][19] .…”
mentioning
confidence: 99%
“… Cerebrospinal fluid drainage (CSFD) which has a strong evidence basis underpinning its use, reducing the pressure of cerebrospinal fluid (CSF) surrounding the spinal cord and consequently increases spinal cord perfusion [2,[18][19] .…”
mentioning
confidence: 99%
“…In this case, the cerebrospinal fluid drainage should be suspended. 20 In the present study, all patients submitted to a second treatment for repair of previous leaks and those patients who had been submitted to a previous surgical bypass underwent cerebrospinal fluid monitoring and drainage whenever increases in cerebrospinal fluid pressure levels were detected. In most series and comparisons between endovascular and surgical treatments for Stanford type B aortic dissections, endovascular treatment decreases the incidence of definitive paraplegia.…”
Section: Discussionmentioning
confidence: 91%
“…Multivariate logistic regression analysis revealed that preoperative aortic rupture was a significant independent risk factor of SCI (P=0.002; (10). The benefit of prophylactic CSFD in open aortic surgery has been established by 2 meta-analyses (9,11). In TEVAR, the risk of SCI has not been completely established, with reported incidence rates ranging from 3% to 12% (2,12), and spinal cord-protective protocols are less defined than open aortic surgeries.…”
Section: Risk Factor Analysis For Scimentioning
confidence: 99%